Flexural buckling of hot-rolled stainless steel channel section columns and beam-columns : testing and design - Chin, Melvin Xin Yu (Nanyang Technological University, 2021)
This paper carried out an experimental study on the minor axis flexural buckling behaviour and resistance of hot-rolled stainless steel channel section columns and beam-columns. Generally, hot-rolled type steels are much better in terms of the homogenous material property, consistency in hardness and ductility in comparison with the welded and press-braked type steels. To investigate the structural behaviour of hot-rolled stainless steel channel sections, a series of tests were carried out on stainless steel channel section columns under axial compression and channel section beam-columns under combined axial compression and minor axis bending moment. The testing procedure included initial global and local geometric imperfection measurements and pin-ended compression tests about the minor principal axis. These compression tests generated a series of results, including load–mid-height lateral deflection curves, failure loads and deformed failure modes. These results were then summarised to assess the accuracy and consistency of the European code. The conclusion derived from the investigation has shown that (i) the European code predicts unsafe flexural buckling resistance for short and intermediate stainless steel channel section columns under pure compression, (ii) the European code displays a low level of accuracy and consistency for stainless steel channel section beam-columns under combined loading.